Gambaran Histopatologi Organ Jantung Tikus Putih Jantan Galur Wistar (Rattus norvegicus) dalam Uji Toksisitas Akut Kombinasi Ekstrak Daun Jati Belanda (Guazuma ulmifolia Lmk.) dan Kelopak Bunga Rosella (Hibiscus sabdariffa L.) - Novia Hilma; Nuri Nuri; Endah Puspitasari; Indah Yulia Ningsih (Pustaka Kesehatan, 2018)
Jati belanda leaves (Guazuma ulmifolia Lmk.) and Roselle petals (Hibiscus sabdariffa L.) have been known for their activity as antihyperlipidemia with different mechanisms. Combination of these plants was expected to has a synergy effect in reducing cholesterol. However, the toxicity of jati belanda leaves and roselle petals extract combination must be investigated for knowing its safety. Based on the acute toxicity test, the LD50 value of jati belanda leaves and roselle petals extract combination was >5,000 mg/kg bw. It was classified as category 5 or unclassified. This research aimed to study about its effect in cardiac by cardiac histopathology examinations of the rats. The result showed that there was no cardiac histopathology changes of the rats at doses 5,000 mg/kg bw. Keywords: jati belanda leaves, roselle petals, acute toxicity, cardiac histopathology